The use of beaches for tourism business: Comparative study in Mexico: Nuevo Vallarta – Cancun - Sonda de la Rosa, Ricardo; García Morales, Evelyn; Gutiérrez Castro, Ily (Administración y Organizaciones, 2021)
Beaches constitute the most famous attractions at tourist destinations in Mexico, where various activities focused on trade are developed; it is pertinent to know and analyze to project its growth, stagnation, withdrawal, or diversification. The purpose of the research is to perform a comparative analysis of tourism businesses between two tourist destinations in the consolidation phase, Nuevo Vallarta and Cancun, according to the Tourism Lifecycle of Richard Butler’s tourist destinations. The methodology used is qualitatively focused on a case study. In the results section, Cancun and Nuevo Vallarta’s tourist businesses’ similarities and differences are described, marking a similarity in their turns but different in their number. Cancun is the one with the most significant number of tourist businesses. Therefore, the result will serve as input shortly to Cancun or Nuevo Vallarta for future decision-making regarding innovation and strengthening the industry of products and services offered and demanded.